Dossiê de acompanhamento e reconhecimento e titulação de remanescentes de quilombos no Brasil. - Raquel Elias Ferreira Dodge; Marcia Dometila Lima de Cravalho; Maria Eliane Menezes de Farias; Sandra Veronica Cureau; Deborah Macedo Duprat de Britto Pereira; Carlos Frederico Santos (My University, 1998)
Dossiê de acompanhamento e reconhecimento e titulação de remanescentes de quilombos no Brasil.